2020
DOI: 10.1002/acr2.11195
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Hospitalization and In‐Hospital Mortality in Adult Systemic Lupus Erythematosus

Abstract: Objective. Systemic lupus erythematosus (SLE) is an autoimmune disease with an increased risk of hospitalization. Multiple studies have reported SLE flare, infection, and cardiovascular (CV) events as the most common reasons for hospitalization. The aim of this study was to use a large US population-based database to comprehensively analyze all indications for adult SLE hospitalization and reasons for in-hospital mortality. Methods. We conducted a retrospective study of SLE hospitalizations in 2017 from the Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Although several studies have determined that individuals with SLE experience higher mortality than the general population (1,2), less is known about the causes contributing to death. Similar to prior research (17,19,20), this study found CVD to be among the top causes of mortality among individuals with SLE. CVD risk in individuals with SLE is not fully explained by traditional risk factors (21).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although several studies have determined that individuals with SLE experience higher mortality than the general population (1,2), less is known about the causes contributing to death. Similar to prior research (17,19,20), this study found CVD to be among the top causes of mortality among individuals with SLE. CVD risk in individuals with SLE is not fully explained by traditional risk factors (21).…”
Section: Discussionsupporting
confidence: 87%
“…Manadan et al used data from the National Inpatient Sample and found that infections accounted for 37% of deaths, followed by CVD (21%) (17). Among our population‐based study of individuals with SLE, CVD was listed as the underlying cause of death for 33% of individuals, followed by rheumatic disease (18%); infections represented only 2% of deaths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies conducted on other rheumatic diseases, it has been seen in similarity to pSS patients that disease activation and infection were the main reasons for hospitalization. The most common causes of hospitalization in SLE patients are SLE flares and organ involvement, infection, cardiovascular system diseases, and pregnancy-related conditions [ 9 , 15 , 16 , 20 , 21 ], whereas those in SSc patients are SSc-related causes (PAH, ILD, digital ulcer, renal crisis), infection, and heart failure [ 17 , 18 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a risk factor for cardiovascular disease (CVD), which has emerged as a leading cause of death in this population ( 1 , 2 , 3 , 4 , 5 , 6 ). CVD can lead to major adverse cardiac events (MACE) after surgery.…”
Section: Introductionmentioning
confidence: 99%